Emotional Maturity with Hate Speech Behavior in Late Adolescents - Mardia, Eka; Aisha, Dinda; Dimala, Cempaka Putrie (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
Hate speech behavior is now common, as seen from the rise of individuals who use abusive language or swear words that are actually inappropriate to say and do when interacting with others. This can certainly affect individual behavior, especially late adolescents and can trigger the development of new languages and negative behaviors such as hate speech. One of the factors influencing hate speech behavior is emotional maturity. This study aims to see the influence of emotional maturity on hate speech behavior in late adolescents in Karawang. The method used is a quantitative approach. The measuring tools used are the hate speech scale and the emotional maturity scale. The sample of this study amounted to 302 respondents. The sampling technique uses non-probability techniques with snowball sampling techniques. Data analysis techniques in this study use normality tests, linearity tests, hypothesis tests with simple regression analysis, determination coefficient tests and categorization tests. The results in this study showed that the emotional maturity variable had a regression coefficient value of -0.434 with a significance of 0.000 < 0.05 which means that emotional maturity has a negative and significant effect on the value of hate speech. It is known that the variable of emotional maturity has a contribution of (4.4%) to influence hate speech behavior in late adolescents in Karawang. The rest (95.6%) were influenced by other variables not studied in the study. The implications obtained in this study are expected to provide information to adolescents to be more able to contribute practically by honing the ability to control emotions and be able to adapt to the sausage environment in order to avoid negative behaviors such as hate speech.Perilaku ujaran kebencian saat ini sudah sering terjadi, terlihat dari maraknya individu yang menggunakan bahasa kasar atau umpatan kata yang sebenarnya tidak pantas diucapkan dan dilakukan ketika sedang berinteraksi dengan orang lain. Hal tersebut tentunya dapat berpengaruh terhadap perilaku individu khususnya para remaja akhir dan dapat memicu berkembangnya bahasa baru serta perilaku negatif seperti ujaran kebencian. Salah satu faktor yang memengaruhi perilaku ujaran kebencian adalah kematangan emosi. Penelitian ini bertujuan untuk melihat pengaruh kematangan emosi terhadap perilaku ujaran kebencian pada remaja akhir di Karawang. Metode yang digunakan adalah pendekatan kuantitatif. Alat ukur yang digunakan adalah skala ujaran kebencian dan skala kematangan emosi. Sampel penelitian ini berjumlah 302 responden. Teknik pengambilan sampel menggunakan teknik non-probabilitas dengan teknik snowball sampling. Teknik analisis data dalam penelitian ini menggunakan uji normalitas, uji linearitas, uji hipotesis dengan analisis regresi sederhana, uji koefisien determinasi dan uji kategorisasi. Hasil dalam penelitian ini menunjukkan variabel kematangan emosi memiliki nilai koefisien regresi sebesar -0,434 dengan signifikansi 0,000 < 0,05 yang berarti bahwa kematangan emosi berpengaruh negatif dan signifikan terhadap nilai ujaran kebencian. Diketahui bahwa variabel kematangan emosi memiliki kontribusi sebesar (4,4%) untuk memengaruhi perilaku ujaran kebencian pada remaja akhir di Karawang. Sisanya (95,6%) dipengaruhi oleh variabel lain yang tidak diteliti dalam penelitian ini. Implikasi yang didapat dalam penelitian ini yaitu diharapkan dapat memberikan informasi kepada remaja untuk lebih dapat berkontribusi secara praktis dengan mengasah kemampuan dalam mengontrol emosi dan mampu beradaptasi dengan lingkungan sosisal agar dapat menghindari diri dari perilaku negatif seperti ujaran kebencian.